Deliberate self-poisoning: a study in London casualty departments. - Ghodse, A H (1977)
During a prospective study of the whole spectrum of drug-related problems treated in one month by 62 casualty departments in the Greater London area, 949 cases of deliberate self-poisoning were identified. Nearly three-quarters of the patients were under the age of 40 years and in all age groups women outnumbered men. Psychoactive drugs of some sort were used in 673 incidents (71%) and ordinary analgesics and other drugs were used in 252 (27%). The incidence of polydrug overdose (423; 45%) was much higher than that found in other studies. In at least 256 incidents (27%) there was a history of repeated overdose in the previous 12 months. Comparison with other studies showed a steady decline in the use of barbiturates in deliberate self-poisoning but an increase in the use of non-barbiturate hypnotics, minor tranquilisers, and antidepressants.